2022
DOI: 10.1108/meq-12-2021-0283
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic impact on the availability of basic amenities: a comparative analysis of villages of hilly states, India

Abstract: PurposeIndia has taken a successful step towards meeting Sustainable Development Goals (SDG) by providing access to basic amenities such as safe drinking water, waste management, drainage systems and bio-compost pits in households. The purpose of this study is to identify factors that significantly impact access to such basic amenities in villages in two states in the hilly regions of India.Design/methodology/approachVillage-level secondary data collected from the Unnat Bharat Abhiyan (UBA) website has been an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…It can be concluded that the needs of the people of Woro Village for clean water can be fulfilled 100%. This is in accordance with research conducted by (Manisha et al, 2023;Patra et al, 2023) that sanitation development and clean water availability are influenced by good access and providing access to basic amenities such as safe drinking water, waste management, drainage systems and bio-compost pits in households.…”
Section: Environmental Dimensionsupporting
confidence: 91%
“…It can be concluded that the needs of the people of Woro Village for clean water can be fulfilled 100%. This is in accordance with research conducted by (Manisha et al, 2023;Patra et al, 2023) that sanitation development and clean water availability are influenced by good access and providing access to basic amenities such as safe drinking water, waste management, drainage systems and bio-compost pits in households.…”
Section: Environmental Dimensionsupporting
confidence: 91%
“…Lack of infrastructure and resources for the Chenchu community to effectively market and disseminate their products could be a flaw in this strategy limiting their ability to maximize sales and reach a wider consumer base. Socioeconomic factors substantially impact the availability of fundamental necessities, influencing the equitable distribution of water, healthcare, education and accommodation within communities (Patra et al ., 2023).…”
Section: Methodology and Data Analysismentioning
confidence: 99%